2020
DOI: 10.1186/s13071-020-3903-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, genetic characteristics and public health implications of Triatoma rubrofasciata, the vector of Chagas disease in Guangxi, China

Abstract: Background Triatomines are natural vectors of Chagas disease and are mainly prevalent in the Americas. In China, previous data from decades ago showed that there were two species of triatomine bugs, Triatoma rubrofasciata and T. sinica. However, the distribution, genetic characteristics and public health implications of triatomines in China are still relatively unknown. In order to gain knowledge on the distribution, genetic characteristics and public health implications of the triatomines in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Though China is a non-endemic country and no CD cases have been reported yet, we have to improve our capacity in the surveillance of potential risks of the disease transmission, since the vector exists in China. As shown in results from previous surveys, one of the transmission vectors, Triatoma rubrofasciata , has been found in at least five provinces in southern China ( 13 - 14 ). By considering the high mobility between China and the world, CD will be possibly introduced in China.…”
mentioning
confidence: 63%
“…Though China is a non-endemic country and no CD cases have been reported yet, we have to improve our capacity in the surveillance of potential risks of the disease transmission, since the vector exists in China. As shown in results from previous surveys, one of the transmission vectors, Triatoma rubrofasciata , has been found in at least five provinces in southern China ( 13 - 14 ). By considering the high mobility between China and the world, CD will be possibly introduced in China.…”
mentioning
confidence: 63%
“…The widespread distribution of T. rubrofasciata found in our study exceeded the sporadic existing records found in museums and in the literature. For example, in Guangxi, T. rubrofasciata was captured in 13 out of 14 prefecture-level cities; Guilin City was the only exception ( 7 ). For this report, this insect presented dispersion favored by interactions with residential settlements and human activities ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them live in rural regions of Latin America, but due to emigration of population, Chagas disease has increasingly spread to urban areas and non-endemic countries with non-vectorial transmission routes [13]. In addition, some triatomine vectors, especially the cosmopolitan Triatoma rubrofasciata, also show a considerable potential for further geographical expansion [14][15][16]. Unlike in other blood-sucking insects, T. cruzi is not transmitted by the bite but by infectious faeces which are accidentally rubbed into the bite wound.…”
Section: Introductionmentioning
confidence: 99%